Comparative genome sequencing reveals insights into the dynamics of Wolbachia in native and invasive cherry fruit flies. Issue 23 (7th May 2021) - Wolfe, Thomas M.; Bruzzese, Daniel J.; Klasson, Lisa; Corretto, Erika; Lečić, Sonja; Stauffer, Christian; Feder, Jeffrey L.; Schuler, Hannes
Abstract: Wolbachia is a maternally inherited obligate endosymbiont that can induce a wide spectrum of effects in its host, ranging from mutualism to reproductive parasitism. At the genomic level, recombination within and between strains, transposable elements, and horizontal transfer of strains between host species make Wolbachia an evolutionarily dynamic bacterial system. The invasive cherry fruit fly Rhagoletis cingulata arrived in Europe from North America 40 years ago, where it now co‐occurs with the native cherry pest R . cerasi . This shared distribution has been proposed to have led to the horizontal transfer of different Wolbachia strains between the two species. To better understand transmission dynamics, we performed a comparative genome study of the strain w Cin2 in its native United States and invasive European populations of R . cingulata with w Cer2 in European R . cerasi . Previous multilocus sequence genotyping (MLST) of six genes implied that the source of w Cer2 in R . cerasi was w Cin2 from R . cingulata . However, we report genomic evidence discounting the recent horizontal transfer hypothesis for the origin of w Cer2. Despite near identical sequences for the MLST markers, substantial sequence differences for other loci were found between w Cer2 and w Cin2, as well as structural rearrangements, and differences in prophage, repetitive element, gene content, and cytoplasmic incompatibility inducing genes. Our study highlights the need for whole‐genome sequencing rather than relying on MLST markers for resolving Wolbachia strains and assessing their evolutionary dynamics.